Generalized Concatenated Polar Auto-Encoder: A Deep Learning Based Polar Coding Scheme - Saber, Hamid; Bae, Jung Hyun (IEEE Global Communications Conference (Online), 2024)
We propose a channel auto-encoder which incorporates the encoding and decoding structure of classical generalized concatenated code (GCC) based on polar codes. The outer encoder and decoder of classical GCC polar codes are implemented by non-linear functions parameterized with a transformer based neural network. Our results show that the proposed scheme results in enhanced reliability of classical polar codes under SC decoding.